Asesmen Sumatif dalam Pembelajaran Bahasa Indonesia Fase D Kurikulum Merdeka - Rahmawati, Laili Etika; Kalaamiyah, Khaafidhatul (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
The aim of this research is to describe the implementation of summative assessment in the Indonesian language learning reading element phase D. Data collection uses observation, interviews and documentation. The object of this research is summative assessment in Indonesian language learning. The subjects of this research were Indonesian language teachers and class VIII students at SMP Muhammadiyah Surakarta. The data used is a summative assessment in the Indonesian language learning material for reading element phase D. The data source was obtained from the implementation of summative assessment in Indonesian language learning for reading element phase D class VIII at SMP Muhammadiyah Surakarta. Data analysis uses descriptive methods. The data analysis technique used includes three stages, namely 1. Data reduction; 2. Data display; 3. Drawing conclusion. The findings show that summative assessments are carried out at the end of every semester. Summative assessment is carried out at the end of the odd semester through the Final Semester Assessment (PAS). There are four types of questions in the Final Semester Assessment (PAS), namely multiple choice questions, true or false statements, matching, and essays. The total number of questions is 50 questions which are divided into several types of questions. There are 25 multiple choice questions, 10 true and false statements, 10 matching questions, and 5 essay questions.